Development of Quality Management in Public Administration of the Republic of Slovenia - A Case Study - Zurga, Dr. Gordana (Prabandhan: Indian Journal of Management, 2011)
In the paper, development of quality management in public administration in Slovenia is presented - the context and main characteristics. General approach as the combination of ’top down’ and ’bottom up’ approaches is explained, with four areas of activities presented more in detail: Common Assessment Framework - CAF, customers and employees satisfaction surveys, training, and annual quality conferences, with emphasized importance of networking and co-operation. Since the late 1990s, when a systematic approach in this respect was initiated, important developments have been